Sexually Transmitted Diseases and Pre-exposure Prophylaxis (PrEP) to HIV Systematic Review - Contreras Vera, Sofía Lorena; Laube, Dr. Gerardo (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Sexually transmitted infections (STDs) constitute a group of very frequent diseases worldwide and an important public health problem. Currently, the positivity of new cases is alarming, which is why it is necessary to renew the preventive strategies and awareness of STDs together with pre-exposure prophylaxis (PrEP) that has proven to be not only effective but also profitable and safe. Objectives: The objective of this Systematic Review of the literature is to evaluate, through the study of scientific publications, the impact, safety, efficacy and controversies that arise from patients with sexually transmitted diseases who are under PrEP therapy for HIV and identify the barriers that exist in the adequate information on the part of the population. Materials and methods: In this systematic review of the literature, research articles published to date on various platforms available on the Internet such as PubMed, Google Schoolar, MedLine, ResearchGate are analyzed in order to obtain reliable data that relationships of sexually transmitted diseases in people on PrEP therapy